Teaching the Complexity of Dependence With the Triplet Game. Issue 3 (1st September 2020) - Burke, Jon; Goukasian, Levon; Shearer, Robert
Abstract: Students often struggle with the concept of dependence of events or random variables. We present a simple coin flipping game that yields surprising results due to the dependencies within the game. The game is simple enough for young children to understand and play, yet complex enough to yield results that are counterintuitive to even most graduate students. We discuss how to implement the game in a classroom, suggest two problems from the game for students to solve, and present several solutions to the problems.